Book Review of White Folks: Race and Identity in Rural America - Patrick Shannon (Journal of Research in Rural Education, 2017)
The 2020 U.S. census (if funded) is likely to confi rm the increased racial diversity of rural (urban and suburban) America, pressuring "whiteness" to assume more aggressive strategies to maintain its status and privileges. At present, we suff er many such examples, from the overt demonstrations in Charlottesville, Virginia; to the veiled eff orts to re-segregate schools in Gardendale, Alabama; to the nearly opaque increases in use of the word "nigger" in Google searches that run along the western side of the Appalachian chain. White Folks can help rural researchers and teachers make sense of these and other daily practices, see the complexities within the identities of the people engaged, and recognize the roles of place in learning to be "White."